Synthesis and characterization of BaLuF5: Tb3+ oxyfluoride glass ceramics as nanocomposite scintillator for X-ray imaging. Issue 15 (15th November 2016) - Cao, JiangKun; Chen, WeiPing; Chen, LiPing; Sun, XinYuan; Guo, Hai
Abstract: Tb 3+ -dopedoxy-fluoride glass ceramics (GC) containing BaLuF5 nanocrystals were manufactured successfully by melt-quenching method with further thermal treatment. Their micro-structural and optical properties were investigated systemically by X-ray diffraction (XRD), transmission electron microscopy (TEM), high-resolution TEM (HRTEM) techniques, transmittance spectra, photoluminescence (PL), luminescence lifetime measurements and X-ray excited luminescence (XEL). PL and XEL from BaLuF5 :Tb 3+ GC are both highly enhanced after further thermal treatment benefiting from the preferential incorporation of Tb 3+ ions into the crystallized BaLuF5 nanocrystals with low phonon energy. Impressively, the integrated XEL intensity for GC640 is about 26% of the commercial BGO scintillator. Our investigation indicates that such Tb 3+ -doped transparent BaLuF5 GC are potential candidates of X-ray scintillators for slow event detection.